Application of electromechanical impedance-based SHM for damage detection in bolted pipeline connection. Issue 1 (2nd January 2016) - Martowicz, Adam; Sendecki, Arkadiusz; Salamon, Marcin; Rosiek, Mateusz; Uhl, Tadeusz
Abstract : The work discusses the effectiveness of the electromechanical impedance-based Structural Health Monitoring system for damage detection in a laboratory test stand – a bolted pipeline section. The impedance-based system developed by the authors and equipped with 12 piezoelectric transducers was used to acquire the data. Different damage scenarios related to loosened bolts and measurement configurations are analysed. Both point and transfer frequency response functions are applied to deterministic and stochastic damage metrics, which are used to assess the condition of the monitored structure. The thresholds levels are proposed for different measurement configurations. Moreover, the authors discuss the perspective to determine the size and localisation of a damage. As confirmed in the work, the stochastic damage metric, preferably applied with a transfer frequency response, is found as of the most practical significance for the tested structure. The carried out analyses consider an outlier removal technique, which becomes necessary to prevent from errors due to temporary variation of the acquired characteristics after initialisation of the measurements.